The forest frontier in the Global South: Climate change policies and the promise of development and equity - Brockhaus, Maria; Gregorio, M. di; Djoudi, H.; Moeliono, M.; Pham Thu Thuy; Wong, Grace Y. (Springer, 2021)
Halting forest loss and achieving sustainable development in an equitable manner require state, non-state actors, and entire societies in the Global North and South to tackle deeply established patterns of inequality and power relations embedded in forest frontiers. Forest and climate governance in the Global South can provide an avenue for the transformational change needed—yet, does it? We analyse the politics and power in four cases of mitigation, adaptation, and development arenas. We use a political economy lens to explore the transformations taking place when climate policy meets specific forest frontiers in the Global South, where international, national and local institutions, interests, ideas, and information are at play. We argue that lasting and equitable outcomes will require a strong discursive shift within dominant institutions and among policy actors to redress policies that place responsibilities and burdens on local people in the Global South, while benefits from deforestation and maladaptation are taken elsewhere. What is missing is a shared transformational objective and priority to keep forests standing among all those involved from afar in the major forest frontiers in the tropics.